Development of Mobile-Based Science Learning Solar System Application to Improve Student Learning Outcomes - Zamzami, Fieki Hilyah; Pradana, Mochamad Desta; Anggraini, Atika (LP2M STIT Palapa Nusantara, 2025)
This research and development project addresses the issue of low student performance in science, particularly on the topic of the solar system, which is attributed to a lack of engaging and effective learning resources. The primary objective is to evaluate the feasibility and effectiveness of a mobile application-based learning medium in improving student learning outcomes. The study adopts the ADDIE model comprising analysis, design, development, implementation, and evaluation as its methodological framework within the Research and Development (R&D) paradigm. Data were collected through tests and questionnaires, with analysis conducted using parametric t-tests and Likert scales. Validation results indicated high feasibility, with scores of 96.6% for content, 75.8% for media, and 95.94% for user testing involving 30 seventh-grade students. The effectiveness test revealed a statistically significant improvement (p = 0.000 < 0.005) between pretest and posttest scores, with an N-Gain score of 0.6742, indicating a moderate effect. These findings demonstrate that mobile-based learning media are both practical and effective in enhancing science instruction on the solar system. The study recommends broader integration of mobile-based tools to enrich interactive learning experiences in science education.